2023
DOI: 10.2106/jbjs.rvw.22.00181
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Pediatric Anxiety During Orthopaedic Cast Room Procedures

Abstract: Background:Cast room procedures can be a source of considerable distress for pediatric patients. High levels of anxiety can make it difficult to perform procedures effectively and may negatively affect the doctor-patient relationship. We sought to evaluate available interventions to reduce anxiety in pediatric patients undergoing orthopaedic cast room procedures.Methods:Following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines, we performed a systematic review to answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In their systematic and critical analysis review, Burkhart et al reported that the majority of cast-room procedures to reduce fear and stress were inexpensive, readily applicable to the clinical setting, and of negligible risk to the patient [ 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their systematic and critical analysis review, Burkhart et al reported that the majority of cast-room procedures to reduce fear and stress were inexpensive, readily applicable to the clinical setting, and of negligible risk to the patient [ 73 ].…”
Section: Introductionmentioning
confidence: 99%